THE GLOBALIZATION EFFECT OF LAW AND ECONOMIC ON CYBERCRIME - Advento Jeronimo (UNISSULA, 2019)
The globalization of law and the economy has led to developing countries' regulations on investment, trade, services, information technology, and other economic fields approaching developed countries (convergence), as well as the regulation of cyberspace activities that cannot be separated from relations with other countries. Norms of law between nations increasingly play an important role, especially how to regulate all forms of advancement in information technology, communication, and transportation. This is inseparable from the foreign policy that has been woven between nations so far. The regulation of cybercrime in legislation is absolutely necessary. Related to the jurisdiction of this crime which is a global crime, it is necessary to have its own law governing cybercrime, namely cyber law, which also regulates its jurisdiction by including the principle that allows cybercriminals to harm the state even though it is outside the state territory.